Food governance in Territorial Short Food Supply Chains: Different narratives and strategies from Colombia and Spain. - Reina-Usuga, Liliana; De Haro-Giménez, Tomás; Parra-López, Carlos (Elsevier, 2020)
Traditional approaches and debates in Agrifood Governance (AFG) have focused exclusively on the role of market forces and public policies. The emergence of alternative food movements, such as Territorial Short Food Supply Chains (TSFSCs), suggest the need to re-evaluate the role of civil society as a driver of governance mechanisms and a source of innovation and transformation of agrifood systems. This paper analyses the AFG processes that are configured in TSFSCs based on social discourses and coordination mechanisms of agents design. For this, the Q method and an exploratory/descriptive analysis are used, and the cities of Bogotá (Colombia) and Córdoba (Spain) are taken as case studies. Results show five different social discourses around AFG: 1) food activism, 2) development cooperation, 3) market niche, 4) local self-management, and 5) social and ecological awareness. It is also noted that TSFSCs configure a mode of reflexive food governance. Coordination mechanisms of the SFSCs are mainly settled in the social and market sphere, and they are in line with features of governance network. These two governance approaches (reflexive and networked) operate in tandem, with important complementary and synergistic effects that foster food democracy.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/14107
Keywords: Alimentos - Abastecimiento - España; Alimentos - Abastecimiento - Colombia; Política alimentaria; Reflexive governance; Q methodology; Alternative food networks; Short food supply chain; Territory; Food democracy